2008
DOI: 10.1590/s0102-09352008000300034
|View full text |Cite
|
Sign up to set email alerts
|

Stress in Salminus brasiliensis fingerlings due to different densities and times of transportation

Abstract: The stress in dorado fingerlings (Salminus brasiliensis) caused by transportation at densities of 5, 10, and 15g/l after 4, 8, and 12h was evaluated by the concentration of tissue cortisol measured by ELISA. The conditions of transportation were simulated on an orbital table shaker with horizontal movements, inside 15 litres plastic bags filled with 4 litres of water and pure oxygen. Cortisol concentrations increased in all densities after 4h of transportation converging to a common concentration at the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…A similar result was reported in a previous study of the same species using juveniles with an average weight of 2.52 g stocked at a density of 54 animals in 5 L of water for 7.5 hours . Moreover, similar results were found by Adamante et al (2008) who recommended 12-hour transportation at a density of 15 g fish L -1 for juvenile S. brasiliensis with an average weight of 0.71 g. The absence of mortality during transportation found in this study was also recorded for pirarucu (Arapaima gigas), but with a shorter transportation time of 3 hours (Brandão, Gomes, Crescêncio, & Carvalho, 2008). Therefore, the present study can contribute to the success of fish farming programmes of juvenile pacamã using long-term transportation.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…A similar result was reported in a previous study of the same species using juveniles with an average weight of 2.52 g stocked at a density of 54 animals in 5 L of water for 7.5 hours . Moreover, similar results were found by Adamante et al (2008) who recommended 12-hour transportation at a density of 15 g fish L -1 for juvenile S. brasiliensis with an average weight of 0.71 g. The absence of mortality during transportation found in this study was also recorded for pirarucu (Arapaima gigas), but with a shorter transportation time of 3 hours (Brandão, Gomes, Crescêncio, & Carvalho, 2008). Therefore, the present study can contribute to the success of fish farming programmes of juvenile pacamã using long-term transportation.…”
Section: Resultssupporting
confidence: 89%
“…The result of our study reveals the need for other studies of juvenile L. alexandri that evaluate higher densities and longer transportation times associated with different water temperatures. In the transportation of juvenile dourado Salminus brasiliensis at different densities (5, 10, and 15g L -1 ) and times up to 12 hours duration, the pH and dissolved oxygen were not affected, but increased fish density resulted in higher ammonia levels at the end of the transportation (Adamante, Nuñer, Barcellos, Soso, & Finco, 2008). The survival rate immediately after 11 hours transportation was 100% for all treatments (Table 2).…”
Section: Resultsmentioning
confidence: 97%
“…These findings corroborate with Seidelin, Madsen, Byrialsen, and Kristiansen (1999), who reported that increased electric conductivity is due to loss of ions from the fish to the water during transportation in response to stressing factors. In a study on the transportation of Salminus brasiliensis, Adamante, Nuñer, Barcellos, Soso, and Finco (2008) reported an increase in the electric conductivity during the first hours of transportation at high stock density. Even with the possible loss of ions, the values observed in this study are probably within the normal range for this species, as high mortality rates were not found even though electric conductivity was increased.…”
Section: Discussionmentioning
confidence: 98%
“…In spite of its advantages, production in net cages may induce stress in fish, due to the increased animal density per cubic meter of water (Adamante et al, 2008). However, several growth enhancers have been used to improve the muscle development of the animals through better nutrients in the diet and higher yield so that the negative effects of intensive production can be eliminated.…”
Section: Introductionmentioning
confidence: 99%